THE POLITICAL INFORMATION TO PROTEST: AN ASSESSMENT OF TOPICAL SOCIAL MEDIA USAGE IN CONTENTIOUS POLITICS - Mercea, Dan (AoIR Selected Papers of Internet Research, 2018)
This article leverages social media and survey data to probe the scope and depth of political knowledge possessed by participants in the Romanian 2017 #rezist protests. For several months, demonstrators gathered in town squares around the country to oppose a project law intended to water down penalties for corruption in high office. Against the backdrop of well-founded scepticism regarding exposure to and engagement with political knowledge on social media, we scrutinize the social media usage of protestors with an interest in the formulation and circulation of political knowledge. We find evidence of applied political knowledge as a prominent component of public activist communication on Facebook. An examination of the network structure further revealed bottlenecks in the circulation and brokerage of knowledge, a result that helps qualify the aforementioned scepticism.